Variations in cephalic vein venography for device implantation–Relationship to success rate of lead implantation - Takashi Tokano (Journal of Arrhythmia, 2013)
Introduction: Lead implantation using the cephalic vein (CV) cutdown technique has been well established, but is not always expected to achieve high success rates. We studied the relationship between preoperative CV venography and the success rate of lead implantation. Methods: Two hundred and twenty one CV venographies were performed in 205 patients (mean age 75 years, 113 males). Leads were inserted via the CV cutdown technique with a guidewire and sheath. Variations in CV venography included usage of the right and left CVs. The success rate of lead implantation was studied. Results: No major kink was observed in 71% of the right CV cases and 43% of the left CV cases. Leads were successfully implanted in over 90% of these patients. A major kink in the CV was found in 15% of the right CV cases and 34% of the left CV cases and successful lead implantation was around 80% in this population. The overall success rate tended to be higher for the right side (83%) than for the left side (71%). Conclusion: Severe kinks or variations in the CV that hinder lead manipulation were less frequent in the right CV. Therefore, a higher success rate of lead implantation by the cutdown technique is expected for the right CV.